Colony Lift Colorimetric Assay for β-Galactosidase Activity - Fuxman Bass, Juan I. (Cold Spring Harb Protoc, 2016)
In this protocol, we present a qualitative assay for monitoring the level of expression of β-galactosidase, an enzyme encoded by the LacZ gene, in yeast. This is useful both for determining autoactivity of LacZ expression in yeast DNA “bait” strains and for assessing LacZ reporter gene activation mediated by a transcription factor “prey” interaction with a DNA bait of interest in yeast one-hybrid (Y1H) assays. In this colorimetric assay, yeast are lysed in liquid nitrogen and then assayed for β-galactosidase expression using the colorless compound X-gal, which turns blue in the presence of this enzyme.